Soil mechanical scarification increases the dry matter yield of cover crops under no-tillage - Do Nascimento, Vagner; Arf, Orivaldo [UNESP]; Alves, Marlene Cristina [UNESP]; de Souza, Epitácio José; da Silva, Paulo Ricardo Teodoro; Kaneko, Flávio Hiroshi; Sabundjian, Michelle Traete; Filho, Marcelo Carvalho Minhoto Teixeira [UNESP]; Galindo, Fernando Shintate [UNESP] (SciELO Agencia Nacional de Investigacion y Desarrollo (ANID), 2019)
Soil mechanical scarification (MS) and cover crop growing (CC) are strategies to minimize compaction in the soil surface layer under the no-tillage system (NTS). The objective of this study was to evaluate the effects of soil mechanic scarification on the yield and nutrient accumulation in the shoot dry matter of cover crops, as well as the persistence of crop residues in NTS, implemented 12 years ago in the Cerrado conditions with low altitude. The study was carried out in Selvíria, Mato Grosso do Sul state, Brazil, in the 2012 and 2013 harvest, in a clay soil classified as Oxisol Red epi-eutrophic alic. The experimental design was a randomized block arranged in a 5 × 2 factorial scheme, with four replicates. The treatments were constituted by the combination of four cover crops (Cajanus cajan, Crotalaria juncea, Urochloa ruziziensis and Pennisetum glaucum) and fallow with spontaneous vegetation, with or without MS. Soil MS increases the shoot dry matter yield of P. glaucum, U. ruziziensis and C. cajan in the first crop. The P. glaucum species, independently of soil scarification, provide higher yield and accumulation of macronutrients in the shoot dry matter, besides provide higher persistence of crop residues. The U. ruziziensis and C. cajan, independently of soil scarification, have the potential for accumulation of N, P, K and Ca in the shoot dry matter, although with less persistence of residues on the soil surface.
Efecto de la escarificación mecánica del suelo en el rendimento de cultivos de cobertura con cero labranza
Keywords: Green manure; Nutrient accumulation; Persistence of crop residues; Soil compaction; Soil conservation management